Analisis Strategi Promosi Program Sahabat Wakaf pada Lembaga Gerakan Wakaf Indonesia (GWI) Sidoarjo, Jawa Timur - Fathoni, Khoirul; Anila, Lia Nor (Management of Zakat and Waqf Journal (MAZAWA), 2021)
This study seeks to reveal a waqf asset marketing strategy model through a program that is eaten with the Friends Program Promotion. The main target of this activity is community, that is, by referring to the hypothesis that waqf assets can develop if supported by human resources, one way is to use waqf assets to be owned by everyone, both as partners and ambassadors. The reason is that the waqf assets are not well known by the public so that many waqf assets are not managed. In addition, the waqf assets contain more certificate conflicts because they have not been properly recorded by the waqf institution. Therefore, this study wants to offer a strategy to promote the development of waqf assets. This research is qualitative with a descriptive approach. Data collection techniques are through observation, interviews, audio and visual media and literature review. The results of the research that have been carried out are as follows: (1) the Indonesian Waqf Movement institute in carrying out a promotion strategy for the waqf companions program, namely by informing and introducing this waqf companion program through printed media (brochures, pamphlets and magazines) and the internet (Instagram, Twitter, Facebook and WhatsApp), (2) in implementing the promotion strategy of the waqf companions program, the Indonesian Waqf Movement institute collaborated with various well-known campuses by holding seminars on endowment companions, (3) promotions that have been formulated and implemented are running quite well, although there are still some a factor that becomes a barrier but this can be a note for the Indonesian Waqf Movement institution in carrying out promotional strategies in the future.